2004
DOI: 10.1128/jvi.78.8.4268-4277.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Template Strand Switching during Initiation and Termination of DNA Replication of Porcine Circovirus

Abstract: Nucleotide substitution mutagenesis was conducted to investigate the importance of the inverted repeats (palindrome) at the origin of DNA replication (Ori) of porcine circovirus type 1 (PCV1). Viral genomes with engineered mutations on either arm or both arms of the palindrome were not impaired in protein synthesis and yielded infectious progeny viruses with restored or new palindromes. Thus, a flanking palindrome at the Ori was not essential for initiation of DNA replication, but one was generated inevitably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
(39 reference statements)
3
24
0
Order By: Relevance
“…Although some of the progeny viruses recovered from the right-arm deletion genomes could be accounted for by sequence duplication caused by slippage of the replication machineries (vRD3.3, vRD3.4, vRD3.5, and vDel3) (10), template strand switching during initiation of DNA replication was evident in vRD1, vRD2a, vRD2b, vRD3.1, vRD3.2, and vRD10. These results prominently display the inverted repeat correction mechanism inherent in the rollingcircle melting-pot replication model (4). The LD7 and LD11 progeny viruses provided the best examples to support this model by exhibiting template strand switching in the middle of synthesizing the left arm and unequivocally demonstrated that both the minus genome and the newly synthesized strand a N were available simultaneously to serve as templates during termination of DNA replication.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Although some of the progeny viruses recovered from the right-arm deletion genomes could be accounted for by sequence duplication caused by slippage of the replication machineries (vRD3.3, vRD3.4, vRD3.5, and vDel3) (10), template strand switching during initiation of DNA replication was evident in vRD1, vRD2a, vRD2b, vRD3.1, vRD3.2, and vRD10. These results prominently display the inverted repeat correction mechanism inherent in the rollingcircle melting-pot replication model (4). The LD7 and LD11 progeny viruses provided the best examples to support this model by exhibiting template strand switching in the middle of synthesizing the left arm and unequivocally demonstrated that both the minus genome and the newly synthesized strand a N were available simultaneously to serve as templates during termination of DNA replication.…”
Section: Discussionmentioning
confidence: 70%
“…Mutant genomes with deletions of three or fewer nucleotides (RD1, RD2a, RD2b, RD3, and Del3) yielded progeny viruses consistently, while a seven-nucleotide-deletion genome (RD7) did not give any progeny virus, and a 10-nucleotide-deletion genome (RD10) yielded infectious viruses only occasionally. In comparison with a previous study (4), nucleotide substitutions engineered into the right arm, left arm, or both arms of the palindrome did not affect protein synthesis or progeny virus production. Therefore, the types of mutations and their specific locations at the origin have different effects on PCV protein synthesis, self-DNA replication, and progeny virus regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations